Advances in polymeric nano-delivery systems targeting hair follicles for the treatment of acne - Yujing Lei; Wanting Jiang; Cheng Peng; Donghai Wu; Jing Wu; Yiling Xu; Hong Yan; Xinhua Xia (Taylor & Francis Group, 2024)
Acne is a common chronic inflammatory disorder of the sebaceous gland in the hair follicle. Commonly used external medications cause skin irritation, and the transdermal capacity is weak, making it difficult to penetrate the cuticle skin barrier. Hair follicles can aid in the breakdown of this barrier. As nanomaterials progress, polymer-based nanocarriers are routinely used for hair follicle drug delivery to treat acne and other skin issues. Based on the physiological and anatomical characteristics of hair follicles, this paper discusses factors affecting hair follicle delivery by polymer nanocarriers, summarizes the common combination technology to improve the targeting of hair follicles by carriers, and finally reviews the most recent research progress of different polymer nanodrug-delivery systems for the treatment of acne by targeting hair follicles.